Formation of the Educational Trajectory: Educational Motives and Choices in the Narratives of Students from Moscow Leading Universities - A. V. Noskova; D. V. Goloukhova; E. I. Kuzmina (Высшее образование в России, 2023)
Motives  and  choices  related  to  obtaining  higher  education  represent  a  pressing  issue that occupies its own niche in the research agenda of the sociology of education and related scientific disciplines. The purpose of the article is to reveal the specifics of the formation of different types of educational trajectories from the perspective of the motives of primary and secondary educational choices of students from top-rated universities. The research question was formulated around differences in goal setting and motivational and value bases of choice when constructing different types of university trajectories  – linear and nonlinear.The  collection  of  empirical  information  was  carried  out  through  interviews  with  40  students achieved the higher GPA from Moscow top-rated universities (MSU, MGIMO, HSE, MVTU, etc.).  Informants described their subjective educational experience as a sequence of choices they made in the space of higher education.Analysis  of  students’  narratives  made  it  possible  to  qualitatively  differentiate  between  linear  and  nonlinear  trajectories,  as  well  as  their  subtypes,  differing  in  their  internal  motivation and educational settings. The analysis identified common motivational reasons for choosing a university and majors at the “entrance” to higher education, as well as motives for secondary educational choice specific to different types of university trajectories — motives for keeping and motives for changing a specialty and university. In the informants’ narratives, choosing a university is described as a complex, multimotivated action, in which the motives of prestige, self-development, as well as social and utilitarian motives are highlighted. Educational choices related to keeping or changing the educational trajectory are determined by the desire to avoid risks and having a high level of satisfaction with studies in the case of linear trajectories and the desire  to  gain  new  educational  experience,  obtaining  competencies  that  go  beyond  the  scope of the specialty being studied, as well as environmental factors of the university in the case of non-linear tracks.It is shown that a qualitative research strategy allows the researchers to look at reflected educational choices from the perspective of their semantic content, which is especially in demand due to the growing trend towards individualization of the educational process. It is concluded that empirical knowledge about the motives and methods of shaping the educational trajectories of the current generation of students is necessary for the development of an effective social and educational environment of a modern university, focused on a student-centered approach to learning.